... And if this was a Zinner's syndrome? - Massimiliano Silveri; Antonio Zaccara; Mauro Colajacomo; Ennio Matarazzo; Francesca Diomedi Camassei; Mario De Gennaro (Elsevier, 2014)
A two year-old male was seen to our Emergency Department for acute abdominal pain, urinary retention and worsening constipation. A first level diagnostic imaging showed a pelvic cystic mass between bladder and rectum. Left kidney was absent. Further workup with MRI and endoscopy demonstrated the cyst to be of urogenital origin. Rapid increase in size and clinical symptoms prompted surgery. Pathology and surgical specimen showed the mass to be a left seminal vesicle cyst secondary to a malformation of the eiaculatory duct and embriologically related to ipsilateral renal agenesis. Such findings were consistent with the diagnosis of Zinner's syndrome (a clinical triad consisting of seminal vesicle cyst, ejaculatory duct obstruction and ipsilateral renal agenesis). Since the symptoms related to the seminal vesicle cyst coincide with the onset of a sexually active life, the majority of cases are generally observed and treated in the second and third decade. To our knowledge, this is the first case description in pediatric age.